Ultra-processed foods have the worst nutrient profile, yet they are the most available packaged products in a sample of New Zealand supermarkets. Issue 3 (29th July 2015) - Luiten, Claire M; Steenhuis, Ingrid HM; Eyles, Helen; Ni Mhurchu, Cliona; Waterlander, Wilma E
Abstract: Objective: To examine the availability of packaged food products in New Zealand supermarkets by level of industrial processing, nutrient profiling score (NPSC), price (energy, unit and serving costs) and brand variety. Design: Secondary analysis of cross-sectional survey data on packaged supermarket food and non-alcoholic beverages. Products were classified according to level of industrial processing (minimally, culinary and ultra-processed) and their NPSC. Setting: Packaged foods available in four major supermarkets in Auckland, New Zealand. Subjects: Packaged supermarket food products for the years 2011 and 2013. Results: The majority (84 % in 2011 and 83 % in 2013) of packaged foods were classified as ultra-processed. A significant positive association was found between the level of industrial processing and NPSC, i.e. ultra-processed foods had a worse nutrient profile (NPSC=11·63) than culinary processed foods (NPSC=7·95), which in turn had a worse nutrient profile than minimally processed foods (NPSC=3·27), P <0·001. No clear associations were observed between the three price measures and level of processing. The study observed many variations of virtually the same product. The ten largest food manufacturers produced 35 % of all packaged foods available. Conclusions: In New Zealand supermarkets, ultra-processed foods comprise the largest proportion of packaged foods and are less healthy than less processed foods. The lack of significant price difference between ultra- and less processed foods suggests ultra-processed foods might provide time-poor consumers with more value for money. These findings highlight the need to improve the supermarket food supply by reducing numbers of ultra-processed foods and by reformulating products to improve their nutritional profile.